Experimental investigation of a building-integrated, transparent, concentrating photovoltaic and thermal collector. (October 2021) - Novelli, Nick; Phillips, Kenton; Shultz, Justin; Derby, Melanie M.; Salvas, Ryan; Craft, Jesse; Stark, Peter; Jensen, Michael; Derby, Stephen; Dyson, Anna
Abstract: As buildings consume roughly one-third of global primary energy, more effective strategies are required to convert on-site solar energy. Here, a multifunctional building façade system, using less than 1% of the semiconductor materials of conventional systems, was tested and developed to expand opportunities for net-zero commercial architecture by synergistically reducing cooling loads, lighting loads, and contributions to urban heat island effects, while converting ambient solar energy resources for internal demands. The B uilding I ntegrated, T ransparent, C oncentrating, P hotovoltaic and T hermal collector (BITCoPT) optically separates diffuse and direct irradiance, transmitting diffuse light for illumination and views. Here, direct irradiance (which is often rejected in commercial buildings to control glare and cooling loads) is intercepted by BITCoPT and converted into electricity and thermal energy. A prototype was tested, demonstrating 43.6% cogeneration efficiency (at a 58 °C operating temperature) relative to direct normal irradiance transmitted through the building's exterior glazing, and 39.0% at 70 °C (which could supply active thermal processes at nominal coefficients of performance). An analytical model was calibrated with observed data, showing good correlation. By substituting parameter values for projected upgrades (to optics, cell type and exterior glazing) into the BITCoPT model, simulated cogeneration efficiency increased to 71.2% at 70 °C (31.2% electrical, 40.0% thermal). Graphical abstract: Image 1 Highlights: Electricity and thermal output measured from transparent, concentrating façade-integrated solar collector. Observed results show good agreement with analytical model. Cogeneration efficiency of 43.6% observed at 58 °C working temperature. Efficiency increases projected with expected photovoltaics, lens assembly, and glazing refinements.